On Representations of C*-Algebras On, α of the Cuntz Type - Sergienko, U. O. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We show that Cuntz-type algebras O n, k, n ≥ k ≥ 2, and O n, k + 1/2, n ≥ 4, k ≥ 2, are *-wild (this implies that the description of all *-representations of these algebras is a very complicated problem).